An experiment on the perceived efficacy of fear-based messages in online roulette. Issue 3 (2nd September 2022) - Mutti-Packer, Seema; Kim, Hyoun S.; McGrath, Daniel S.; Ritchie, Emma V.; Wohl, Michael J. A.; Rockloff, Matthew; Hodgins, David C.
ABSTRACT: The current study examined the emotional and cognitive evaluations as well as the perceived efficacy of fear-based, text-only pop-up messages. The pop-up messages were presented when viewing a 3-minute prerecorded video of online roulette play. Fifty-nine people who gamble online viewed both low- and high-threat messages that reflected, by random assignment, either the financial ( n = 27) or social ( n = 32) consequences of gambling. Participants then reported their emotional and cognitive evaluations of the messages, as well as their perceived efficacy to facilitate responsible gambling. Eye-tracking was used as an objective measure of attention to the message. A 2 (message theme: social, financial) x 2 (threat level: low, high) mixed-model ANOVA was used to examine the evaluations and efficacy of the messages. The main effects of message theme/threat level were not significant. The 2 × 2 interaction for the outcome of overall effectiveness was significant, whereby the high-threat and social message combination was rated more effective than other combinations. For eye-tracking, there were no significant findings. The results suggest that fear-based social messaging may be more effective than non-fear inducing or financially-oriented messages. Further research can explore if messages that are perceived to be effective likewise lead to lower-risk gambling.